Potensi Interaksi Obat Pada Pasien Asma Rawat Inap Di Rsud Dr. Moewardi Tahun 2014 - Setyorini, Nurita, Nurul Mutmainah, M.Si., Apt (2016)
Asthma is one of the biggest causes of morbidity and mortality in the world. Treatment of asthma in some patiens has not shown results optimally. The aim of this study was to describe about potential drug interactions in patients hospitalized with asthma in the hospital X 2014. This is a non-experimental research with retrospective data collection. Data was analyeze descriptively. Samples were collected with inclusion criteria i.e. patients diagnosed with asthma, receiving at least two medications that used at the same time, and complete medical record data. There was 95 samples collected. Samples were analyzed to get an overview of potential drug interactions from the level of seriousness and the mechanism of interactions based on literature "Drug Interaction Facts" and http://www.drugs.com/drug_interactions.html database. Anti-asthma medications most commonly prescribed were corticosteroid i.e. methylprednisolone (58 prescriptions), xanthine derivate i.e. aminophylline (47 prescriptions), simpatomimetic i.e. salbutamol (42 prescriptions), anticholinergic i.e. ipratropium bromide (26 prescriptions), and other medication i.e. n-acetylcystein (32 prescriptions). The result showed there were 512 cases (77,89%) of potential drug interactions in 74 patiens out of 95 patient samples. The level of seriousness of potential drug interactions were 9,18% major, 65,82% moderate, and 25% minor. The mechanism of interactions of potential drug interactions were 52,34% pharmacodynamic mechanism, 29,09% pharmacokinetic mechanism, and 18,62% unknown mechanism. The most frequent drug interactions is aminophylline with metylprednisolone 25 cases (4,88%, n = 512).